An Analysis of Critical Education Study on Independent Learning Campus Policy - Amirudin, Amirudin; Tjalla, Awaludin; Indrajit, Richardus Eko (Universitas Pahlawan Tuanku Tambusai, 2022)
Critical education is education that is able to free from ignorance, poverty, oppression, and lift the condition of the subject from the pits of oppression and helplessness, both human and environmental. Freedom to learn is an idea where the educational paradigm is not confined and has a meaning that is freer than the freedom of life. The purpose of this study is to describe a critical educational analysis of the policy of independent campus learning in Indonesia. The research methodology used is library research, using the following steps: knowing and finding out the type of library needed, reading the type of library needed, conducting an assessment, presenting the results of the literature study. The sources of this research are research journals, books and the internet. The results showed that the campus policy of independent learning, independent learning supports the realization of critical education. This can be seen from the programs launched in the policy where students are required to be creative, critical and dare to apply their knowledge in a real form. Students voluntarily (can take or not) to get their rights such as internships.